Normative methodology of science: Karl Popper (1902 - 1994) and Hans Albert - Pandit, Giridhari L. (Begegnungen mit Hans Albert, 2019)
Karl R. Popper was a great admirer and friend of Hans Albert. What is it exactly that connected them ? Answer to this question, barely a sketch, will also answer the question why and how I came to know Hans Albert. Within the normative methodological tradition set forth in Rene Descartes’ Regulae (1628) and Discourse on the Method (1637), Karl R. Popper and Hans Albert converged on critical rationalism, the generalized version of Popper’s deductivist-falsificationist methodology of science (Popper 1934).